2011
DOI: 10.1534/genetics.111.131227
|View full text |Cite
|
Sign up to set email alerts
|

UNC-73/Trio RhoGEF-2 Activity Modulates Caenorhabditis elegans Motility Through Changes in Neurotransmitter Signaling Upstream of the GSA-1/Gαs Pathway

Abstract: Rho-family GTPases play regulatory roles in many fundamental cellular processes. Caenorhabditis elegans UNC-73 RhoGEF isoforms function in axon guidance, cell migration, muscle arm extension, phagocytosis, and neurotransmission by activating either Rac or Rho GTPase subfamilies. Multiple differentially expressed UNC-73 isoforms contain a Rac-specific RhoGEF-1 domain, a Rho-specific RhoGEF-2 domain, or both domains. The UNC-73E RhoGEF-2 isoform is activated by the G-protein subunit Ga q and is required for norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 95 publications
(177 reference statements)
4
19
0
Order By: Relevance
“…Hence, we next tested the corresponding upstream G protein GSA-1 and the phosphodiesterase PDE-4, a negative regulator of Ga S signaling, for their effects on locomotor activity. Consistent with previous reports (Charlie et al 2006;Hu et al 2011), the two Ga S (gf) mutant alleles gsa-1(ce94) and pde-4(ce268) also showed enhanced swimming and spontaneous crawling activity similar to that of kin-2(cau1) and kin-2(ce179) (Figure 1, A-C).…”
Section: Resultssupporting
confidence: 91%
“…Hence, we next tested the corresponding upstream G protein GSA-1 and the phosphodiesterase PDE-4, a negative regulator of Ga S signaling, for their effects on locomotor activity. Consistent with previous reports (Charlie et al 2006;Hu et al 2011), the two Ga S (gf) mutant alleles gsa-1(ce94) and pde-4(ce268) also showed enhanced swimming and spontaneous crawling activity similar to that of kin-2(cau1) and kin-2(ce179) (Figure 1, A-C).…”
Section: Resultssupporting
confidence: 91%
“…In contrast, a different isoform, UNC-73E, which contains only the RhoGEF domain, activates Rho GTPases and regulates both cell migration and locomotion (26,27). We found that missense mutations u908 and rh40 and splice donor mutation e936, which all alter UNC-73B, resulted in shortened ANs from both the PLM and ALM.…”
Section: Significancementioning
confidence: 78%
“…Therefore, we cannot pinpoint the PLC-3 site of action. It was reported that UNC-73 has EGL-30-independent functions regulating locomotive behaviors in neurons other than motor neurons (17). It would be interesting to find whether PLC-3 also functions in those cells.…”
Section: Discussionmentioning
confidence: 95%
“…A later study argued that the Rho GEF domain of UNC-73/Trio (referred to as UNC-73 hereafter) was the other EGL-30/Gαq target (15). It was suggested that UNC-73 functions in parallel or downstream of the DAG kinase DGK-1 and inhibits the conversion of DAG to phosphatidic acid (16,17). Although this explains how UNC-73 stabilizes DAG once it is produced, it remains unclear how UNC-73 regulates the production of DAG.…”
Section: Resultsmentioning
confidence: 99%